Identifying Barriers to Smoking Cessation in Rheumatoid Arthritis. Issue 5 (May 2015) - Aimer, Pip; Stamp, Lisa; Stebbings, Simon; Valentino, Natalia; Cameron, Vicky; Treharne, Gareth J.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to investigate disease‐related issues that make smoking cessation challenging for patients with rheumatoid arthritis (RA). There is currently a lack of research on tailoring smoking cessation interventions for RA patients. Qualitative exploration is a necessary first step in planning targeted interventions. Methods A qualitative mixed‐methods study was undertaken. Participants attended either a focus group or an individual interview and completed a set of standardized questionnaires. The sample consisted of 36 RA patients: 24 current smokers and 12 ex‐smokers. The transcripts were analyzed thematically using a critical realist approach to inductively identify themes. Results Five key barriers to smoking cessation that are faced by RA patients were identified. First, participants were unaware of the relationship between smoking and RA and therefore did not perceive this as a reason to quit. Second, smoking was used as a distraction from pain. Third, participants found it difficult to exercise and therefore were unable to use exercise as an alternative distraction. Fourth, smoking was used as a coping mechanism for the frustrations of living with RA. Fifth, participants felt unsupported and isolated from other RA patients. Conclusion Disease‐related issues may hinder smoking cessation for RA patients. Through an understanding of patients' perspectives there is an opportunity to plan an effective targeted intervention that may increase the chance of smoking cessation in RA patients where smoking may adversely influence disease progression and comorbidities.